Living with a diagnosis of frontotemporal dementia: An interpretative phenomenological analysis. (April 2023) - Gray, Suzanne; Shepherd, Ashley; Robertson, Jane
Frontotemporal dementia describes a spectrum of disorders which include behavioural changes, changes to affect, speech difficulties and physical issues. Although literature exists which identifies the need for the voices of people with dementia to be heard, there is a paucity of research which includes hearing the experiences of people diagnosed with FTD. The purpose of this research was to explore the lived experience of frontotemporal dementia from the persons' perspective using interpretative phenomenological analysis. The themes that emerged in the analysis were: the rocky road through assessment; the changing self; in touch with reality; and keeping going. Two overarching themes emerged which were: the need to hear the voice of people with frontotemporal dementia; and for people with frontotemporal dementia to exercise some control over the decision making process throughout their journey. Recommendations are presented for future practice and research.